Physiological response of soybean [Glycine max L. Merril] genotypes to drought-induced stress: preliminary screening for drought under south sudan agro-ecological (Ironstone/Mountains) conditions - Gama, P.B.S.; Vuga, A.J.; Chigeza, G. (2020)
Drought stress is a major environmental factor that adversely limits the growth and the production of crops. In order to screen 18 soybean genotypes, an experiment was conducted in University of Juba, (CNRES), Department of Agricultural Sciences Experimental Unit with an objective of screening 18 soybean accessions/genotypes for drought tolerance at two separate experiments (non-drought stress and drought stress sites) based on randomized complete block design (RCBD) with three replications. The data were collected on plant height (cm), root length (cm), biological yield (biomass in g), number of pods per plant, number of aborted pods, number of seeds per plant, seed weight per plant (g), Grain yield per plot (2.5 m2), Harvest index (HI) and 100 seed-weight (g) at harvest. The result showed that drought stress is an important factor in growth and yield reduction especially when drought stress occur at reproductive stages such as initial pod filing, beginning of seed formation and full seed stages is responsible for yield reduction compared to non drought stress conditions. Furthermore, the results also indicated that drought stress affect all the morphological and reproductive parameters and the significant differences exist among the soybean accessions at (P<0.05) under both non- drought stress (ND) and drought stress (DS) conditions except, root length under non drought stress and the harvest index under drought stress condition. Drought stress also decreased the plant height and dry weight by 15% and 48.3% respectively and increased the root length by 19.4% and also adversely reduced the reproductive components such as number of pods/plant (44%), number of seeds/plant (58.4%), seed weight/plant (55%), grain yield/plant (60.3%), 100-seed weight (17.4%) and harvest index (24.4%). The most affected parameter by drought stress was the yield/plot by 60.3% reduction. Moreover, the results also indicated clearly that the effect of drought stress on the final yield was due to reduction in reproductive components. Although drought stress had great impact on the final grain yield, some accessions such as TGx 2010–15F, TGx 2006–3F, TGx 2008–4F, TGx 2010–12F, TGx 2008–12F, TGx 2004–3F, TGx 2007–11F were less affected by drought stress as they showed high yield under both non-drought stress (ND) and drought stress (DS) conditions hence exhibit tolerant to drought stress. This clearly indicated that the respond of different accessions to drought stress varies from one accession to another and identify the following TGx 2004–13F, TGx 1987–62F, TGx 1448–2E, TGx 2010–3F, TGx 1485–1D, Local–107 as drought susceptible. It should be noted that, the narrow genetic diversity in the soybean accessions would likely not provide a wider genetic variability in response to drought stress. The latter suggests further research and use of more accessions from other regions or agro-ecological zones.